Ordered structures of poly(butylene 2, 5-thiophenedicarboxylate) and their impact on material functional properties. (September 2018) - Guidotti, Giulia; Gigli, Matteo; Soccio, Michelina; Lotti, Nadia; Gazzano, Massimo; Siracusa, Valentina; Munari, Andrea
Graphical abstract: Highlights: Two different raw materials have been used for the synthesis of PBTF. Due to amount and nature of ordered domains, PBTF properties have been modulated. Amount of mesophase determines the mechanical and gas permeability behavior of PBTF. Three PBTF polymorphs have been described and their stability evaluated. Abstract: In this contribution, the effect of ordered structures on the functional properties of poly(butylene 2, 5-thiophenedicarboxylate) (PBTF) has been studied. By employing a different raw material, i.e. dimethyl-2, 5-thiophenedicarboxylate instead of 2, 5-thiophenedicarboxylic acid, it has been possible to modulate PBTF mechanical properties and gas permeability, owing to a different degree of crystallinity and amount of mesophase. Furthermore, PBTF polymorphism is unveiled as three different crystalline structures have been described. The most thermodynamically stable structure has been also identified.